Efektivitas Problem Based Learning Berbantuan LKPD Interaktif terhadap Berpikir Logis Matematis Siswa - Hayati, Mutiara Nur; Rhomdani, Rohmad Wahid (Universitas Sultan Ageng Tirtayasa, 2025)
This purpose of this study was to investigate how well a Problem-Based Learning (PBL) model supported by interactive Student Worksheets (LKPD) affected the tenth-grade students at SMA Negeri 5 Jember’s capacity for mathematical logical thought when studying quadratic equations. The experimental class received a PBL implementation based on interactive LKPD, whereas the control group received traditional instruction. According to the post-test analysis result, the experimental class student’s average score of 87,78 on the mathematical logical thinking ability exam was considerably higher than the control class's score of 74,36. According to the findings of the homogeneity test, tcalculated>ttable with a value of 4.84 > 1.99. Additionally, the experimental class outperformed the control class in the logical thinking indicators, with an overall average of 81.86% in the very high category and 65.03% in the high category. The results support the idea that students’ mathematical logical thinking skill can be enhanced by the use of interactive student worksheets (LKPD) in conjunction with the problem based learning (PBL) approach.